Pencatatan Digital dengan Google Forms Pada Koperasi Petani di Karanganyar - Agus Trihandoyo; Satya Arisena Hendrawan; Putriarrum Kusuma Wardani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
In just a few decades, digital technology has revolutionized our way of life. However, its utility has not been fully exploited, particularly among farmer communities, where recordkeeping is virtually non-existent, and if it does exist, it is typically manual and susceptible to data loss. Bumi Intan Pari is an agricultural cooperative, located in Karanganyar Regency, Central Java that connects farmers to markets. The majority of the cooperative's members are organic rice farmers. This partner was selected as part of the research on the analysis of digital technology use within agricultural cooperatives to promote agriculture development. To assist them manage agriculture data recording, we provided the Cooperative’s members with training and management of Google Forms-based digital record keeping. The training emphasized digital recordkeeping for cooperatives and farmers, followed by description of Google Forms and its benefits. Then, the creation of a form relevant to farmers' daily operations. In the exercise, the participants started to create a Google email address, then a Google form. Next, the creation of questions, the selection of response types, form settings, and a preview of the completed form. This training has assisted the cooperative and its members in making their digital devices more useful for agri-business recordkeeping.